To simplify the expression -5(c+d)+7c-2d using the distributive property, we can first distribute the -5 to both terms inside the parentheses:
-5(c+d) = -5c - 5d
Now we can rewrite the expression with the simplified terms:
-5(c+d) + 7c - 2d = -5c - 5d + 7c - 2d
Next, we can combine like terms by combining the coefficients of the same variables:
-5c + 7c = 2c
-5d - 2d = -7d
The simplified expression becomes:
2c - 7d
use the distributive property to combine like terms and simplify the expression -5(c+d)+7c-2d
1 answer